NEW LOCALITIES AND TAXONOMIC REMARKS FOR SOME MOSSES IN CONTINENTAL ANTARCTICA (Ninth Symposium on Polar Biology) - カンダ, ヒロシ; KANDA, Hiroshi (National Institute of Polar Research, 1987)
P(論文) Distribution and taxonomic aspects of four moss species occurring in Continental Antarctica are discussed. Bryoerythrophyllum recurvirostre (HEDW.) CHEN and Pottia heimii (HEDW.) HAMPE were found in several localities of Vestfold Hills, Princess Elizabeth Land. The former species was collected again 30 years after it was first collected at Vestfold Hills and the latter was recorded in the same area for the first time. Pottia austro-georgica CARD, was collected in Amundsen Bay, Enderby Land, which is the second record in Continental Antarctica. Grimmia lawiana J. H. WILLIS was newly collected on the Sor Rondane Mountains, Queen Maud Land. Distribution maps and illustrations of these species are given. departmental bulletin paper